The Importance of Similar Devices in Alisher Navoi’s Poetry - Umarova Nargizakhon Rustamovna; Mumtozbegim Karimjonova Anvarjon qizi; Umarova Hilolakhon Ilkhom qizi (Genius Journals, 2022)
This article discusses the composition of the simulators used in Navoi ghazals. In Navoi’s poems, it is reported that simulations are formed using three different grammatical devices and that they have unequal opportunities in the formation of simulators. In Navoi’s poetry, examples of extended analogies are given and analyzed, and the importance of the study of analogies in linguistics in general is highlighted
Keywords: Analogy; analogy; extended; morphological